Enhancing Investment Strategies: A Comprehensive Technical Analysis Approach for Informed Buy-Sell-Hold Decisions in NEPSE (Nepal Stock Exchange) - Joshi, Dushyant Lal (Nepal Journal of Multidisciplinary Research, 2023)
Stock price forecasting is a type of time series issue that anticipates a company's condition based on an analysis of time values. To address the Buy-Sell-Hold problem, investors need to make accurate predictions about future indices or stock price changes. In this study, data was collected for 6 months (February 2023 to July 2023), and technical trading tools such as candlesticks, Bollinger Band, and MACD were used. While personal views of respondents were taken from Google Form Questionnaire Surveys to determine the Buy-Sell-Hold in NEPSE. A questionnaire survey yielded 62 responses. A combined chart of Candle Sticks, BB, and MACD gives better results compared to the analysis of a single technical indicator. This data shows that 70.97% agreed that the technical analysis gives the right path and decision, and the rest 29.03% did not agree with the technical analysis to predict the Buy-Sell-Hold decisions. However, seeing the statically, real distribution of the "Buy-Sell-Hold" would be helpful for a fuller analysis and understanding of the data. These analyses can be favourable to the good economic and political condition of Nepal.